Can C-reactive protein inform antidepressant medication selection in depressed outpatients? Findings from the CO-MED trial. (April 2017) - Jha, Manish K.; Minhajuddin, Abu; Gadad, Bharathi S.; Greer, Tracy; Grannemann, Bruce; Soyombo, Abigail; Mayes, Taryn L.; Rush, A. John; Trivedi, Madhukar H.
Highlights: Pre-treatment C-reactive protein (CRP) levels predict differential response to currently available antidepressant treatments. Depressed patients with low CRP level (<1 mg/L) respond better to SSRI monotherapy whereas those with higher levels respond better to combination of bupropion and SSRI. A CRP threshold (< or ≥1 mg/L) based treatment assignment, as compared to random treatment allocation, will require treatment of 8.6 depressed patients for 1 additional remission. Abstract: Objective: Currently, no valid measures inform treatment selection for depressed patients. Whether C-reactive protein (CRP) in particular and two other acute phase reactants (inflammatory markers) could differentiate between patients responding to either of two treatments with different mechanisms of action was assessed. Method: Subjects included Combining Medications to Enhance Depression Outcomes (CO-MED) trial participants randomly assigned to either escitalopram plus placebo (SSRI monotherapy, n = 51) or bupropion plus escitalopram combination (bupropion-SSRI combination, n = 55) with baseline plasma samples. CRP, serum amyloid P component, and alpha-2-macroglobulin were measured using the Bioplex Pro™ human acute-phase 4-plex panel. We conducted mixed model analyses of depressive symptom (Quick Inventory of Depressive Symptomatology Self-Report) and side-effect burden (Frequency, Intensity, and Burden of Side-Effects Rating Scale) obtained weekly or every other week over the 12-week acute-phase of CO-MED trial to evaluate the relationship between these outcomes and baseline CRP and other acute-phase reactants. Results: The treatment arms did not differ in depressive symptom or side effect outcomes. Most participants (69.8%, 74/106) had baseline CRP levels greater than 1 mg/L (indicative of systemic inflammatory activity). Higher baseline CRP levels were associated lower depression severity (correlation coefficient = −0.63) with bupropion-SSRI combination but not with SSRI monotherapy (correlation coefficient = 0.40). The overall remission rate was 41.5%. The estimated remission rate with CRP threshold based assignment (SSRI monotherapy for <1 mg/L and Bupropion-SSRI for ≥1 mg/L) was 53.1%, with a number needed to treat of 8.6. Side effect burden was unrelated to any baseline inflammatory marker. Conclusions: Baseline CRP levels relate differentially to antidepressant treatment outcomes in persons with major depressive disorder. Clinicaltrials.gov identifier: NCT00590863